THE URGENCY OF ENTREPRENEURSHIP EDUCATION BY UTILIZING DIGITAL TECHNOLOGY FOR UIN ALAUDDIN MAKASSAR STUDENTS - Suban, Alwan; Gani, Ilham (Idaarah: Jurnal Manajemen Pendidikan, 2024)
Entrepreneurship education is a weapon that destroys action and poverty, and becomes a ladder towards the dream of every student to be financially independent. This study aims to determine the Urgency of Entrepreneurship Education by Utilizing Digital Technology for UIN Alauddin Makassar Students. The results of this study indicate that entrepreneurship education is needed in any field regardless of the field occupied or one's profession. With entrepreneurship education students are able to build an entrepreneurial spirit by creating various creative ideas and innovations, being able to utilize and follow the very rapid developments of digital technology. The conclusion of this study is Entrepreneurship Education at UIN Alauddin Makassar Higher Education as a process or activity carried out in order to internalize entrepreneurial mentality, transmit entrepreneurial knowledge and skills to students, accelerate experience and transmit the mindset and behavior of an entrepreneur to students so that they behave and become entrepreneurs. This is very important because the development of entrepreneurship has led to a creative and digital economy, so that it is able to make new businesses no longer focus on finding work and becoming workers anymore, but can create and open jobs.